The relationship between vitamin D levels, D-dimer and platelet parameter levels in patients with gestational hypertension - Wang, Pingping; Yao, Jin; Li, Yaqiong; Zhang, Zhanjun; Zhang, Ruiling; Lu, Shouting; Sun, Meixia; Huang, Xiaorong (Frontiers in Immunology, 2025)
IntroductionHypertension during pregnancy is a common pregnancy complication that has an important impact on maternal and fetal health. In recent years, studies have shown that vitamin D, D dimers and platelet parameters may play a key role in the occurrence and development of gestational hypertension.ObjectiveThis study aimed to explore the relationship between vitamin D levels, D dimers and platelet parameters in patients with gestational hypertension.Material and methodsThis study retrospectively analyzed the clinical data of 90 patients with gestational hypertension and 90 normal pregnant women who were treated in our hospital from September 2022 to September 2023. We compared the blood routine indicators between the two groups, including platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW), etc., as well as D dimer and vitamin D (Vit D) levels.ResultsThe results showed that the vitamin D level and PLT in the gestational hypertension group were significantly lower than those in the normal pregnant group, while MPV and PDW were significantly increased. In addition, vitamin D levels were significantly correlated with D dimer, MPV and PDW. Further statistical analysis showed that vitamin D, D dimer and platelet parameters were important predictors of gestational hypertension.ConclusionThis study found that patients with gestational hypertension have vitamin D deficiency and abnormal platelet function. Vitamin D may affect the development of the disease by regulating platelet activity and coagulation status, which may be closely related to its pathological mechanism. This suggests that improving vitamin D status may have potential value in the management of gestational hypertension.